Factors associated with institutional delivery among the rural women in Bangladesh - Das, Akkur Chandra; Biswas, Manaj Kumar (Mediscope, 2016)
Maternal mortality and morbidity rates in Bangladesh along with poor health care access are still high. The aim of this study was to identify associated factors with institutional delivery among rural women in Bangladesh. The cross sectional study conducted among the rural women aged 15-49 years old in seven sub-districts of Bhola district, Bangladesh. The study sample size was 250 rural women who were purposively selected. Hazards Model Analysis, namely univariate (Model 1) and multivariate (Model 2) binary logistic regression analyses, was performed in the final analysis. Employing the hazards analysis, the study had identified that the maternal characteristics such as mothers education, age, and media exposure were more important covariates associated in explaining institutional delivery (Model 1). Education of mother, exposure of media, and family income were strongly and positively associated with the risk of termination of institutional delivery in the both Model 1 and Model 2. Mothers with higher education have a positive significant effect on the termination of institutional delivery, when compared with women of education below secondary. The findings of the present study are likely to the government and policy makers to take appropriate measures to decrease delivery complexities and mortalities by increasing institutional delivery facility where the facility is lacking. Mediscope Vol. 3, No. 2: July 2016, Pages 18-25